Printing Leibniz's Calculus: Dating and Numbering the Editions of the Nova Methodus pro Maximis et Minimis (October 1684). (10th June 2021) - Lemley, Samuel V
Abstract: The textual history of the first work on infinitesimal calculus and differentiation in print—Gottfried Wilhelm Leibniz's 'Nova methodus pro maximis et minimis …' in the October 1684 instalment of the Leipzig scientific journal Acta Eruditorum —remains unstudied. Consequent to this inattention, extant copies of Leibniz's article have been assigned to a single edition and a single press, despite evidence of substantive variation among them. This article examines the typographic and bibliographical evidence across multiple copies of the October 1684 instalment of the Acta to demonstrate that these extant copies in fact represent three separate editions printed on multiple presses over many years. This evidence, in turn, casts new light on both the complex printing history of the Acta Eruditorum in its first decade of publication (1682–93) and the distribution of learned periodicals in the seventeenth century.